Multilocus sequence typing for Candida albicans strains from the intestinal tract of patients with cirrhosis - Zhu, J; Cao, J-F; Zhang, T; Li, T-Y; Li, X-W; Shen, W (European review for medical and pharmacological sciences, 2018)
Multilocus sequence typing (MLST) was applied to investigate the genetic diversity of Candida albicans in the intestinal tract of cirrhosis patients. We used CHROM agar Candida medium to obtain 105 Candida sp. isolates from fecal samples (276 subjects), including 63 isolates from the cirrhosis group (141 subjects) and 42 isolates from the healthy control group (135 subjects). Among the 105 Candida strains isolated, 60 strains were identified as Candida albicans. Patients with cirrhosis had significantly higher rates of colonization by Candida sp. (44.68% vs. 31.11%, p < 0.05) and C. albicans (27.66% vs. 15.56%, p < 0.05) relative to healthy controls. In the cirrhosis group, the rate of colonization further increased with disease progression and antibiotic treatment (p < 0.01). Sixty C. albicans isolates were analyzed by MLST. Fifty diploid sequence types (DST) were observed, and 26 new DSTs and 3 novel alleles were found. The majority of isolates were distributed among three clades, clade 8 (31.67%), clade 14 (15.00%) and clade 18 (21.67%). Among 39 strains from the cirrhosis group, 16 strains (41.02%) belonged to clade 8, while only 3 strains (14.29%) from healthy group belonged to clade 8 (p < 0.05). In addition, concatenated sequences of the 7 housekeeping gene fragments were analyzed for all the different DSTs in clade 8 to evaluate the loss of heterozygosity (LOH), which indicates C. albicans microvariation in the gut of cirrhosis patients. This study suggests that cirrhosis disease progression and antibiotic treatment is associated with increased colonization by Candida sp. and C. albicans. We are the first to provide MLST-based genotype profiles for C. albicans Guizhou China, and to identify clade 8 as the potential main clade of C. albicans colonization in the gut of cirrhosis patients.